2003
DOI: 10.2466/pms.2003.97.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Personality Traits Influence the Difference between Time Taken to Tell the Truth or Lie

Abstract: A necessary component of lying is the withholding of a truthful response. Hence, lying may be conceptualised as involving the inhibition of an initial, automatic response (the truth) while an alternative response (the lie) is generated. We investigated response times to visually and auditorially presented questions probing recent episodic memory, when subjects answered questions truthfully or with lies. We also investigated whether the absolute response times or difference between time taken to tell the truth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…In experiments where the task resembles ours here (that is, constant unelaborated Yes-No responses) the increase in RT for false responses is uniformly reported to be around 200-230 ms (Farrow et al, 2003;Walczyk. 2003, in Yes/No condition;Vendemia et al, 2005) Previous studies have not distinguished between Yes and No responses, and so have not found the interaction that is the most striking aspect of the results here.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In experiments where the task resembles ours here (that is, constant unelaborated Yes-No responses) the increase in RT for false responses is uniformly reported to be around 200-230 ms (Farrow et al, 2003;Walczyk. 2003, in Yes/No condition;Vendemia et al, 2005) Previous studies have not distinguished between Yes and No responses, and so have not found the interaction that is the most striking aspect of the results here.…”
Section: Discussionmentioning
confidence: 55%
“…That lying involves an increase in response time has, as noted in the introduction, been known for well over a century, and has been regularly confirmed in more recent studies (Dorward, 1999;Spence et al, 2001;Alban, 2003;Farrow et al, 2003;Vendemia et al, 2005). The reason for this is, however, in dispute.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations